Jóvenes interactuando con nuevas tecnologías : formas emergentes de aprender inglés (2017)
The new information and communication technologies (ICTs) provide different alternatives in the current teaching and learning scenarios. Therefore, the present document shows how the interaction with these technologies contributed to the English learning of two groups of students of higher grades in two public educational institutions. Through an educational ethnography and with the purpose of understanding the cultural phenomenon in question, fieldwork was carried out, which included a diagnostic questionnaire in its initial phase, followed by class observations, focus groups and the elaboration of diaries by the young participants. The findings evidenced new learning scenarios mediated by ICT in formal and informal contexts of, these last ones enhanced by personal interests to approach English, in addition to a high level of technological appropriation that students demonstrated in the academic context in general. Consequently, the relevance of the study lies in the value of identifying current ways of approaching the English of young people, who through daily practices of interaction with technology developed informal processes of access to the language that many times the teacher does not know, designing activities addressed to specific content in formal educational contexts, without regard to the students interests and skills.--Tomado del Formato de Documento de Grado.